Epoxidation of indene and cyclooctene on nanocrystalline anatase titania catalyst - Ramaswamy, Veda; Awati, Preeti; Ramaswamy, A. V. (Topics in Catalysis, 2006)
Nanocrystalline anatase titania samples of different crystallite sizes were prepared by sol gel method using ultrasonication and calcination at different temperatures. The calcined samples were treated with H2O2 in order to study the role of surface hydroxyl groups present on titania in generating reactive oxygen species responsible for the epoxidation reaction. The crystallite size of the calcined samples increased from 4 to 18 nm as the calcination temperature increased from 473 to 773 K, respectively. More uniform distribution/dispersion of the nanoparticles (SEM), marginally higher surface area, better thermal stability and phase purity are some of the advantages of preparation of nanocrystalline TiO2 by using ultrasonication. EPR spectral data on the H2O2-treated samples confirmed the presence of superoxide radical species. The two distinct UV bands observed at 400 and 450 nm are assigned to charge transfer of peroxide (O-2 2-) to Ti. FT-IR spectral data show that the surface hydroxyl groups are the active sites in the generation of reactive oxygen species. The catalytic activity was evaluated in a series of epoxidation reactions using indene and cyclooctene as substrates and aqueous H2O2 as oxidant. The activity was found to decrease with increase in the calcination temperature of the samples, obviously due to an increase in crystallite size and a decrease in surface hydroxyl groups. The nanoparticle titania samples show better conversion and selectivity than the standard titania (Degussa P-25). The kinetic studies revealed that the reaction followed a pseudo first order kinetics in excess of H2O2.
19th Meeting of the North-American-Catalysis-Society (NAM), Philadelphia, PA, MAY 22-27, 2005
Keywords: cyclooctene epoxidation; epoxidation of indene; nanocrystalline anatase titania; superoxide radical on titania

Effect of fuel and its concentration on the nature of Mn in Mn/CeO2 solid solutions prepared by solution combustion synthesis - Murugan, B.; Ramaswamy, A. V.; Srinivas, D.; Gopinath, Chinnakonda S.; Ramaswamy, Veda (Acta Materialia, 2008)
Nano and microcrystalline, Mn/CeO2 solid solutions (5 mol.% Mn) have been prepared by solution combustion synthesis using urea, glycine or polyethylene glycol (PEG) as fuel. The nature of the fuel and its concentration (fuel to metal mole ratio, F/M have a strong influence on the physical and chemical characteristics of the resulting Mn/CeO2 solid solutions. The variations in the physicochemical properties are attributed to differences in (i) the adiabatic/real flame temperature realized with these fuels at different F/M ratios; (ii) the sustenance of the temperature or the quenching effect of the fuel at higher F/M ratios; (iii) combustion or decomposition of the precursors as the main course of the reaction; and (iv) the generation of gaseous products during combustion. Since the addition of the fuel to the initial precursor solution does not change the pH of the medium, the differences in the type of Mn species formed are mainly attributed to the combustion process. (C) 2007 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Combustion synthesis; Mn-ceria; Nanocomposites; X-ray diffraction (XRD); X-ray photoelectron spectroscopy (XPS)

Enhanced negative thermal expansion in MFI molecular sieves by varying framework composition - Bhange, Deu S.; Ramaswamy, Veda (Microporous and Mesoporous Materials, 2010)
In the present investigations we have carried out the high temperature X-ray diffraction (HTXRD) studies on the metallosilicate molecular sieves iron silicalite-1 (FeS-1) samples of different Si/M ratios (Si/Fe = 50, 75, 100 and infinity) for their negative thermal expansion (NTE) behavior. All the samples exhibit NTE behavior in the temperature range 373-773 K. Systematic increase in negative thermal expansion coefficient is observed as a function of increasing Fe content in the MFI framework. Strength of the negative thermal expansion increases in the order Si/Fe = infinity < 100 < 75 < 50. It is concluded that by changing the composition of the framework of MFI, enhanced negative thermal expansion can be obtained. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: HTXRD; Negative thermal expansion; Silicalite-1